ANALISIS SEMANGAT KERJA PEGAWAI PADA BADAN NARKOTIKA KABUPATEN KUTAI TIMUR - Hidayat, Sarwono (PREDIKSI, 2016)
This study aims to determine and describe the level of employee morale at East Kutai County Narcotics Agency. The approach used in this study is a qualitative descriptive approach. The results showed that all indicators morale has an average value of a good percentage, where the attendance rate of 79.8%, amounting to 86.4% of cooperation, discipline amounted to 82.5%, amounting to 86.7% responsibility and accuracy of 82%. This means that all indicators of morale are in either category. The results showed also that the average value of a variable percentage of morale is 83.5%. Thus it can be concluded that the level of Employee Morale on Narcotics Agency of East Kutai Regency is 83.5% and is included in both categories. This means that the formulation of the problems that exist in this study can be missed.Â